2019
DOI: 10.4236/ojbm.2019.74118
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Successful Implementation of Electronic Procurement in Government Institutions Based on the Technology Acceptance Model

Abstract: Electronic procurement has continued to gain ground in many organisations world over both in government and private institutions as a basis for competitive procurement and good practice. African countries have also started implementing electronic procurement and Zambia is no exception. Electronic procurement when well implemented has many organisational advantages to be gained by respective institutions that implement these reforms. In this paper, the aim was to identify the factors affecting successful implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…An elevated perception of ease of use by the user correlates positively with a higher success rate of using the system. This study supports Karim and Lasena (2017), Tulodo andSolichin (2019), andKademaunga andPhiri (2019). The ease of use of information systems implies that users can operate with greater efficiency and efficacy.…”
Section: Ease Of Use Affects the Success Of Using The E-procurement S...supporting
confidence: 81%
See 1 more Smart Citation
“…An elevated perception of ease of use by the user correlates positively with a higher success rate of using the system. This study supports Karim and Lasena (2017), Tulodo andSolichin (2019), andKademaunga andPhiri (2019). The ease of use of information systems implies that users can operate with greater efficiency and efficacy.…”
Section: Ease Of Use Affects the Success Of Using The E-procurement S...supporting
confidence: 81%
“…Consequently, adopting a new information technology system, particularly e-procurement, is probable. Kademaunga and Phiri (2019) stated that The perception of usefulness significantly influences the implementation of the e-procurement. Karim and Lasena (2017) stated that ease of usage positively impacts User satisfaction with e-procurement.…”
Section: Successful Use Of the E-procurement Systemmentioning
confidence: 99%
“…The findings of this study backed up this hypothesis, indicating that perceived usefulness had a major impact on users' acceptance of e-procurement in the Nigerian public sector. A significant number of studies have demonstrated that perceived usefulness is positively associated with behavioural intention to accept e-procurement (Brandon-Jones & Kauppi, 2018;Kademaunga & Phiri, 2019;Kusuma & Pramunita, 2011;Ramkumar & Jenamani, 2015) and other new technology adoption areas like Internet banking (Astuti, Musadieq, & Utami, 2021), tourism (Hasni, Farah, & Adeel, 2021) and e-learning (Abdullah & Ward, 2016. The results from the current study revealed that users' perception of e-procurement technology is an important factor that determines its effective adoption.…”
Section: Structural Model Resultsmentioning
confidence: 63%
“…Persepsi Kemudahan Penggunaan didefinisikan sebagai sistem yang mudah dipelajari dan digunakan oleh pengguna, atau yang sering disebut ramah pengguna (Chawla, D., & Joshi, 2019). Menurut Kademaunga & Phiri, (2019) Persepsi kemudahan penggunaan adalah tingkat keyakinan seseorang bahwa penggunaan suatu sistem akan terjadi tanpa memerlukan upaya yang berlebihan. Tujuan dari kemudahan penggunaan adalah untuk memastikan bahwa pengguna tidak menghadapi hambatan atau kesulitan yang signifikan saat menggunakan teknologi tersebut.…”
Section: Perceived Ease Of Use (Kemudahan Penggunaan)unclassified